STRATEGI COPYWRITING DALAM KAMPANYE HARI KOPI SEDUNIA DI AKUN INSTAGRAM @PILIGREENNETWORK - Nafi'ah, Maeva; Priatna, Wahyu Budi (Universitas Riau, 2025)
This study analyzes the copywriting strategy of the NGO PILI Green Network during its 2025 World Coffee Day campaign on Instagram (@piligreennetwork) in response to the urgency of environmental communication in digital media. Employing a qualitative-descriptive approach using content observation, interviews, and active participation (internship), this research examines the implementation of the persuasive AIDA framework (Attention, Interest, Desire, Action). The results indicate the strategy’s success in building Attention and Interest through a friendly tone of voice and eco-storytelling that emphasizes Dual Benefits (farmer welfare and forest conservation). However, a significant limitation was found in the Action phase, where Call-to-Action (CTA) tended to be low-effort (interaction) and lacked specificity in encouraging high-effort conversions (e.g., sustainable coffee purchase). This study contributes to non-profit communication practices by highlighting the importance of measurable CTAs to enhance public participation and real sustainability action